The Influence Of 4c Elements In Instagram @Teguk.Indonesia On The Formation Of The Teguk Indonesia Brand Image - Damayanti, Nita Putri; Putri, Ananda Syifa Yustian; Pratama, Muhammad Alvar (GoAcademica Research & Publishing, 2024)
The communication strategy currently employed by many brands involves introducing and promoting their products by leveraging social media platforms like Instagram for online communication and creating a brand image. Teguk Indonesia is a brand in the food and beverage sector in Indonesia with the Instagram account @teguk.indonesia. To shape its brand image, Teguk Indonesia utilizes its Instagram account. The Instagram account features various informative, educational, and entertaining content, and is used for social media marketing as well as communicating with Teguk Indonesia’s customers online. Therefore, this study aims to investigate the influence of the 4C elements on the Instagram account @teguk.indonesia on the formation of Teguk Indonesia’s brand image and the extent of that influence. This study employs a quantitative method and purposive sampling technique involving 100 respondents who are followers of Teguk Indonesia’s Instagram account in filling out the questionnaire. The results show that the 4C elements on the Instagram account @teguk.indonesia influence the formation of Teguk Indonesia’s brand image by 62.8%, with the remaining influence attributed to other factors. This study is expected to serve as a reference for companies or brands in effectively and efficiently utilizing Instagram to shape their brand image.